آليات الاندماج الاجتماعي لذوي الاحتياجات الخاصة (المعاقين) - الورفليأ.نجية أحمد (Aljameai)
المستخلص: هدفت الدراسة إلى وضع تصور يتضمن مجموعة من الآليات تمكن ذوي الاحتياجات الخاصة (التلاميذ المعاقين) من الاندماج تربويا في مدارس التعليم العام. وانطلقت الدراسة من تساؤل مفاده: ما أهم آليات الدمج التربوي للمعاقين في مدارس التعليم العام؟ واستخدمت الدراسة المسح الشامل لمجتمع الدراسة الذي بلغ (90) مفردة من ذوي الاختصاص في مراكز ذوي الاحتياجات الخاصة (المعاقين) في مدينة بنغازي، ولجمع بيانات الدراسة استخدمت استمارة استبانة متضمنة مقياس ليكرث بصيغته الثلاثية، وتوصلت الدراسة إلى مقترح يتضمن مجموعة من آليات التخطيط التي تحدد الاحتياجات التي تخدم عملية الاندماج، بالإضافة إلى مجموعة من آليات تنفيذ خطة الاندماج وفق أساليب محددة، وأخيرا مجموعة من آليات المتابعة والتقييم لمتابعة تنفيذ العمل وسيره وفق الخطة المرسومة لضمان نجاحها. Abstract: The study aimed to develop a vision that includes a set of mechanisms that includes a set of mechanisms that empower people with special needs. Disabled students are able to integrate educationally into general education schools. The study started from a question that stated: what are the mechanisms for educational integration of the disabled into general education schools? The study a comprehensive community survey to study which reached (90) individuals from those specializing in centers for people with special needs (the disabled) in the city of Benghazi. To collect the study data, a questionnaire from used that included Using anon –Likert scale in its tripartite from, the study reached a proposal the merger process, in addition to a set of baht, serves to implement the merger plan according to specific methods. Finally, a group of follow – up and evaluation procedures follows up on the implementation of the work and its progress according to the drawn – up plan to ensure its success.